A lower limb mixed reality system for the elderly - Rodrigues, Luis Guilherme Silva [UNESP]; Brandao, Alexandre Fonseca; Dias, Diego Roberto Colombo; Guimaraes, Marcelo De Paiva; Magna, Thais Sporkens; Fernandes, Paula Teixeira; Brega, Jose Remo Ferreira [UNESP] (Association for Computing Machinery (ACM), 2022)
This work presents a mixed reality system for lower limb exercise that detects the user's gait and synchronizes the Street View navigation in the display. It uses an accessible RGB camera with a computer vision approach to detect the body. 11 Elderly volunteers tested the system for 5 minutes each session while therapists analyzed their physical and cognitive activity. In the meantime, the system stores the motion capture data for later use. We analyzed their behaviors in 20 recorded sessions.
Keywords: augmented reality; healthcare; mixed reality